1990
DOI: 10.1557/proc-212-99
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Alpha and Gamma Radiation on Glass Reaction in an Unsaturated Environment

Abstract: Radiation may effect the long-term performance of glass in an unsaturated repository site by interacting with air, water vapor, or liquid water. The present study examines (1) the effects of alpha or gamma irradiation in a water vapor environment, and (2) the influence of radiolytic products on glass reaction. Results indicate that nitric and organic acids form in an irradiated water vapor environment and are dissolved in thin films of condensed water. Glass samples exposed to these conditions react faster and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…For the irradiated tests, the glass monoliths were doped with Tc-99, and actinides (Np-237, U-238, Pu-239, Am-241) at levels approximating 23 IJ.Ci/g total activity (designated 131A, 165A, 202A tests) [5]. Glass used in the nonirradiated tests were doped with only U-238 (designated 131U, 165U, 202U tests).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the irradiated tests, the glass monoliths were doped with Tc-99, and actinides (Np-237, U-238, Pu-239, Am-241) at levels approximating 23 IJ.Ci/g total activity (designated 131A, 165A, 202A tests) [5]. Glass used in the nonirradiated tests were doped with only U-238 (designated 131U, 165U, 202U tests).…”
Section: Methodsmentioning
confidence: 99%
“…In this type of environment, radiolytic product concentrations may rapidly increase in the limited quantities of water contacting the glass. Previous studies have demonstrated that nitric and organic acids are produced in both alpha and gamma irradiated air + water vapor systems [5]. In such a scenario, the pH buffering capacity of bicarbonate in the thin film of water contacting the sample may be rapidly overwhelmed by the condensation of __ alteration rates [7] and affect the stability of some secondary mineral phases.…”
Section: Introductionmentioning
confidence: 99%
“…This process has been observed in experiments where air and water systems have been exposed to either alpha or gammairradiation (Wronkiewicz et al, 1991b). Although pH decreases resulting from this process may be minor in the relatively low radiation fields produced by UO 2 in the present tests, the abundance of fission products and actinides in spent nuclear fuel would result in a radiation field several orders of magnitude greater than that of UO 2, and thus would lead to conditions where nitrogen acid generation would become enhanced in an actual repository scenario.…”
Section: Non-uranium-bearinqmineralsmentioning
confidence: 80%
“…Solution analyses indicate that inorganic carbon is being converted into organic carbon, whereas total carbon concentrations remain constant (Table 2). The and oxalic acids have been produced in experiments with water condensed on alpha-producing 241Am foils (Wronkiewicz et al, 1991b). Organic species may also play an important role in actinide complexation and migration.…”
Section: Non-uranium-bearinqmineralsmentioning
confidence: 99%
“…The G(NO 3 -) values reported for irradiated oxidized water systems range from zero to less than 0.2 [21-26]. The G values for radiolytic production of nitric acid from moist air or two phase air/liquid water systems range from ~2.0 to 3.0 for gamma, alpha, electron, and mixed neutron-gamma irradiation studies [24,[26][27][28][29][30][31][32]. In these systems, nitric acids that formed in the gas phase were concentrated in the liquid [24,32].…”
Section: Air and Water Radiolysismentioning
confidence: 99%